FREQUENCY OF INJURIES IN BASKETBALL - A SYSTEMATIC REVIEW - Goran Jelaska; Srđan Prodanović; Marta Tomljanović (The Sky)
Basketball is a team sport that is really demanding due to its dynamism and variety of motor, technical and tactical abilities that are necessary for the successful performance of basketball elements. The following databases were used to collect adequate literature: GoogleScholar, PubMed. For the analysis, studies were taken that investigated the frequency of injuries in professional, semi-professional and elite basketball players. In order for the studies to meet the inclusion criteria, they contained complete data on the type of injury, localization, and frequency of injury on the tested sample. The total number of respondents in all surveys was 3,802 respondents from all collected and analyzed previous surveys. In this study, more than 4,260 basketball injuries from 15 analyzed studies were analyzed, and after analyzing the results of these studies, it was noted that the most injuries were in the lower extremities in the amount of (66.6%), and the number of injuries in the ankle joint was (33.6% ), while the second most injured part of the body was the knee (19.4%). As for upper extremity injuries, hand, finger and wrist injuries predominate (7.1%) compared to shoulder, hand and forearm injuries (5.8%). This study found that jumping/landing, turning or stopping, or contact with an opponent are the most common causes of injury in basketball players. It can be said that a large number of injuries can occur due to the increased fatigue of basketball players, so it can also be said that a proper training program can be the best prevention of injuries in basketball players. It is concluded that basketball is a sport with a high frequency of injuries.